Artistas primitivos, ingênuos (naïfs), populares, contemporâneos, afro-brasileiros: Família Silva: um estudo sobre resistência cultural - Büll, Márcia Regina (2007)
Interdisciplinary Study on Arts and History of Culture regarding cultural resistance of primitive, naïf, popular, contemporary, and Afro-Brazilian artists represented by the Silva s Family . Throughout the life-history of its members, collection of public and private document files, bibliography and iconography, the research registers the Silva s cultural diversity, artistic production, and cultural resistence: when facing its own ethnic and racial adversities, in its migratory process, as well as when facing the City of São Paulo s public policies (from 1960 up to 2007), related to Republica s Square Art and Culture Fair. It concludes defining the need of interdisciplinary groups for the selection of art and handcrafts expositors in order to preserve the artistic pole in that site.